PENINGKATAN DAYA SAING SEKOLAH MELALUI STRATEGI GENERIK PORTER: PERAN MULTIPLE INTELLIGENCES RESEARCH (MIR) DALAM INOVASI PEMBELAJARAN BAHASA INGGRIS - Erika Agustiana (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of Porter’s Generic Strategies, namely cost leadership, differentiation, and focus, in improving school competitiveness through English learning based on Multiple Intelligences Research (MIR). This research employed a qualitative approach with a case study design at a private elementary school in East Java. Data were collected through observations, in-depth interviews, and documentation, then analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the three Porter’s strategies were implemented in an integrated manner within school management and learning practices. The cost leadership strategy was reflected in the efficient management of school resources without reducing the quality of educational services. The differentiation strategy was realized through the application of the MIR approach, which improved students’ participation, motivation, and learning outcomes in English learning. Meanwhile, the focus strategy was directed toward fulfilling the needs of parents who prioritize holistic education and early English mastery. The findings confirm that the integration of management strategies and learning innovation contributes significantly to improving school competitiveness in a sustainable manner amid increasingly competitive educational environments.